Elementary School Teachers trying out Mathematical Modeling - Gomes, Joice Caroline Sander Pierobon; Silva, Karina Alessandra Pessoa da; Dalto, Jader Otavio (Universidade Estadual de Campinas, 2020)
In this paper we present and analyze a premier Elementary School teachers’ experience with Mathematical Modeling. The experience related to the problem situation “orange juice” occurred at one meeting of a teachers’ collaborative group, composed by elementary school teachers, undergraduate students of chemistry and mathematics and teacher trainers. The teachers written productions were analyzed, as well as the transcriptions of the audio and video recordings of the meeting. The analysis, based on the development phases of a modeling activity revealed, among other things, that the problems created by a group of teachers, as well as the resolutions, come very close to the classroom routine problems. However, the problems created by teachers from other two groups are closer to expected problems from the perspective of mathematical modeling. Anyway, what we can conjecture is that the activity of mathematical modeling presented a dynamic character, as well as made possible a resignification of the mathematization phase that presented itself in a transversal way in all the orientation made by the teachers.